The Impact of Sigmoid Notch Involvement on the Outcomes of Distal Radius Fractures: Radiological and Clinical Assessments after a Minimum of 5 Years of Follow-up - Kim, Yu-Seok; Lim, Jun-Hyuk; Kim, Myung-Sun (Clinics in orthopedic surgery, 2025)
Posttraumatic osteoarthritis (OA) is one of the complications of distal radius fractures (DRFs). Involvement of the sigmoid notch (SN) is a risk factor, but there are few studies that support this. In this study, we hypothesized that SN involvement can affect the radiological and clinical outcomes of surgically treated DRFs and that there would be differences based on the degree of SN involvement. The authors reviewed patients who underwent surgical treatment for DRF at our institution and were followed up for over 5 years. The patients were divided into 2 groups based on SN involvement. All patients underwent postoperative plain radiographs at the last follow-up to evaluate posttraumatic OA at the distal radioulnar joint (DRUJ). On computed tomography (CT) scans of the SN involvement group, articular step-off and gap distance were measured. Posttraumatic OA was graded using the Knirk and Jupiter radiographic criteria. For clinical evaluation, grip strength, wrist range of motion, pain visual analog scale score, Disabilities of the Arm, Shoulder, and Hand questionnaires, and Modified Mayo Wrist Score were assessed. Radiologically, the DRUJ OA grades were significantly higher in the SN involvement group. The step-off and gap distance measured on CT scans revealed no significant correlation with the grades. Clinical outcomes were not significantly different between the 2 groups. SN involvement did not affect clinical outcomes in DRF patients with a minimum of 5 years of follow-up. However, radiologically, the OA grades were significantly higher in the SN involvement group. Therefore, in cases of DRF with SN involvement, there is no significant difference in clinical outcome, but it is necessary to explain to patients that posttraumatic DRUJ arthritis may occur in the future.